THE INFLUENCE OF JOB INSECURITY ON TURNOVER INTENTIONS THROUGH THE ROLE OF MEDIATING JOB SATISFACTION IN TEXTILE INDUSTRY SOLO DISTRICT, INDONESIA - Didiek Hermawan; Asri Laksmi Riani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The moderate turnover rate of textile industry employees in Solo District, Indonesia, must be prevented early on from employee turnover intentions. Turnover intentions and other antecedent factors are more meaningful to examine because have an excellent predictive effect on actual turnover. This study proposes to empirically analyze the effect of job insecurity on turnover intentions through job satisfaction. This study used primary data collected from 111 textile industry employees from Community College (AK-Tekstil) graduates in Solo District and Structural Equation Model (SEM) with SMART PLS. This study identified that job insecurity has a strong detrimental impact on turnover intentions. However, it has a substantial favorable impact on job satisfaction. This study also found the contribution of a moderate mediating effect of job satisfaction between job insecurity and turnover intentions, and job satisfaction has an adverse influence on turnover intentions. This study has shown that job insecurity can have detrimental effects on turnover intentions even though job satisfaction is still at a moderate level overall because employee satisfaction at work still allows consideration to withdrawal. In addition, different directions of mental evaluation of job satisfaction drive a more extensive evaluation than the insecurity effect. Keywords: Job Insecurity, Job Satisfaction, Turnover Intentions